A comparative study of the effect of physical-social factors on the quality of life of residents of different types of housing in quarantine conditions (Case study: different types of housing in Tehran). - jamaleddin honarvar; sara jalalian (تحقیقات کاربردی علوم جغرافیایی)
Housing, as the primary needs of mankind and providing his satisfaction, plays an essential role in improving the quality of life. In these conditions, the "home quarantine or social distance plan" is the only way to interrupt the transmission chain, this research seeks to examine the physical-social factors in the quality of today's homes (including a variety of species of housing) for long-term presence of humans in The conditions are quarantine. In this paper, we have tried to extract indices and components of the quality of different types of housing and the effect of each of the factors in the tolerance of quarantine conditions in different types of housing of Tehran. The method is based on applied purpose and in terms of descriptive-analytical nature and comparative technique. The documentary and field method and a questionnaire were used to collect information. To analyze the data, single sample t-test and mean test and to study the normalization of data were used by colomogorov-smarinov test. The statistical population of the study includes residents of different types of housing in Tehran are 381 samples. Measurement of research indicators with Likert spectrum and with a assumed average of 3 and 3 indicators and 9 components and 49 measures. These indicators include physical, social, cultural indicators. According to the results, residential complexes have the highest level of satisfaction (mean 4.41) of physical-social factors in the quality of life of residents of different types of housing species in quarantine conditions. The level of social, physical and functional indicators in general for residential complexes show a better condition. By summing up these indices and the overall examination of physical-social factors in the quality of life of residents of different types of housing in terms of quarantine conditions; It was found that apartment housing has the lowest satisfaction (3.77) of social physical factors of their quality of life in quarantine conditions. At the end of research, suggestions for improving the quality of life of residents of different types of housing in quarantine conditions were presented with respect to physical-social dimensions.